2016
DOI: 10.1002/cmdc.201600497
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase Inhibitory Activity: Methyl‐ versus Chlorochalcone Derivatives

Abstract: Numerous studies have shown that chalcones are promising scaffolds for the development of new monoamine oxidase-B (MAO-B) inhibitors. As a continuation of our ongoing research into the development of reversible human MAO-B (hMAO-B) inhibitors, two series of twenty chalcones containing electron-donating and electron-withdrawing substituents were synthesized. All compounds were found to be competitive, selective, and reversible inhibitors of hMAO-B except (2E)-1-(4-methylphenyl)-3-(4-nitrophenyl)prop-2-en-1-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 51 publications
4
27
0
Order By: Relevance
“…The presence of hydroxy and methoxy groups or two hydroxy groups on the ortho and para position of the A aromatic moiety as well as a chlorine atom on the para position of the B ring of chalcones leads to potent MAO−B inhibitory action . Recent studies of our group demonstrated that substitution with chloro or methyl groups on the para substitution of phenyl A system shown potent and reversible type of hMAO−B inhibitors . It is clear that introduction of lipophilic‐electron withdrawing groups such as bromine, chlorine, fluorine and trifluromethyl group on the para position of ring B of chalcones increase the MAO−B inhibitory action.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hydroxy and methoxy groups or two hydroxy groups on the ortho and para position of the A aromatic moiety as well as a chlorine atom on the para position of the B ring of chalcones leads to potent MAO−B inhibitory action . Recent studies of our group demonstrated that substitution with chloro or methyl groups on the para substitution of phenyl A system shown potent and reversible type of hMAO−B inhibitors . It is clear that introduction of lipophilic‐electron withdrawing groups such as bromine, chlorine, fluorine and trifluromethyl group on the para position of ring B of chalcones increase the MAO−B inhibitory action.…”
Section: Introductionmentioning
confidence: 99%
“…This paper investigates the response of voids in reinforced concrete beams. The voided sections were located below the neutral axis as it is more effective [7]. Polystyrene was used as the void former due to its lightweight properties.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts are mainly focused for the development of MAO‐B inhibitors rather than MAO‐A . It has largely been reported that the presence of electron donating or lipophilic groups such as methyl, dimethylamino, ethyl, bromine, fluorine, and trifluoromethyl groups at ring B of chalcones are favorable for MAO‐B inhibitory activity . Simultaneously, the effect of heterocyclic systems such as thiophene, indole, furan, and imidazole in ring A also produced promising MAO‐B inhibitory potencies by maintaining the above‐mentioned pharmacophore on ring B .…”
Section: Introductionmentioning
confidence: 99%